Inclusão de Stylosanthes cv. Campo Grande na silagem de Urochloa brizantha cv. Piatã - Turmina, Roberta (2018)
The objective of this study was to evaluate the nutritional values and fermentation characteristics of Urochloa brizantha silage cv. Piatã with inclusion levels of Stylosanthes cv. Large field. The experimental area was divided into seven plots of 9 m2 with dimensions of 3m x 3m each, where four of these plots were of Urochloa brizantha cv. Piatã and three of Stylosanthes capitata cv. Large field. The experimental design was completely randomized with four treatments and four replications. The inclusion levels of the legume adopted Stylosanthes cv. Campo Grande were 0%, 20%, 40% and 60%. Nutritive and fermentative characteristics of the silages were evaluated. For the fermentation characteristics, there was a linear effect (P<0.05) for dry matter, mineral matter, crude protein (P <0.05) for pH, effluent loss and buffer capacity, lignin in acid detergent and digestibility, in contrast to organic matter, acid detergent fiber and neutral detergent fiber (P <0.05). In the fractionation of protein, there was a quadratic effect (P <0.05) for fractions A and C, while carbohydrate fractionation was observed with increasing linear effect (P<0.05) for soluble carbohydrates, fraction A and fraction C and linear decreasing effect (P <0.05) for fraction B1 and B2. Parameters not mentioned do not mean significance (P> 0.05). The inclusion of the legume improved as fermentative and nutritional characteristics of grass silage.